Karmiloff Smith, A. (1994). Más allá de la modularidad. Madrid. Alianza Editorial. Orig. 1992. pp. 292 - Pilar Bretón Sáenz (Universidad de La Rioja, 2013)
Karmiloff Smith, A. (1994). Más allá de la modularidad. Madrid. Alianza Editorial. Orig. 1992. pp. 292.